The Transcriptome of Schistosoma mansoni Developing Eggs Reveals Key Mediators in Pathogenesis and Life Cycle Propagation - Lu, Zhigang; Sankaranarayanan, Geetha; Rawlinson, Kate A.; Offord, Victoria; Brindley, Paul J.; Berriman, Matthew; Rinaldi, Gabriel (Frontiers in Tropical Diseases, 2021)
Schistosomiasis, the most important helminthic disease of humanity, is caused by infection with parasitic flatworms of the genus Schistosoma. The disease is driven by parasite eggs becoming trapped in host tissues, followed by inflammation and granuloma formation. Despite abundant transcriptome data for most developmental stages of the three main human-infective schistosome species—Schistosoma mansoni, S. japonicum and S. haematobium—the transcriptomic profiles of developing eggs remain under unexplored. In this study, we performed RNAseq of S. mansoni eggs laid in vitro during early and late embryogenesis, days 1-3 and 3-6 post-oviposition, respectively. Analysis of the transcriptomes identified hundreds of up-regulated genes during the later stage, including venom allergen-like (VAL) proteins, well-established host immunomodulators, and genes involved in organogenesis of the miracidium larva. In addition, the transcriptomes of the in vitro laid eggs were compared with existing publicly available RNA-seq datasets from S. mansoni eggs collected from the livers of rodent hosts. Analysis of enriched GO terms and pathway annotations revealed cell division and protein synthesis processes associated with early embryogenesis, whereas cellular metabolic processes, microtubule-based movement, and microtubule cytoskeleton organization were enriched in the later developmental time point. This is the first transcriptomic analysis of S. mansoni embryonic development, and will facilitate our understanding of infection pathogenesis, miracidial development and life cycle progression of schistosomes.